PEMBENTUKAN RESILIENSI (RESILIENT FORMATION) PADA PENDERITA THALASSEMIA - Yudi Kurniawan (Universitas Islam Indonesia, 2016)
Thalassemia is a genetic disorder within hemoglobin formation that cause its patients were given blood transfusion along their life, it make thalassemia patients having difficulties for doing activity and self-actualization. Thalassemia patient in Indonesia increase rapidly within ten years lately (TEMPO magazine January 17th 2010 edition). This research have been used qualitative method with case study design, it is aimed for exploring resilient formation and resilient determinant within thalassemia patients. There are two respondents (thalassemia patient) attain the age of 19 and 20 years old who have been interviewed in this research. Data in this research were collected by in depth interview. Data were analyzed using open and axial coding. Result in this research showed that resilience is formed by four resilient determinants. There are support from significant others, individual spiritual factor, competent factor, and goal-seeking. Resilient formation process consists of resilient determinant key factor, adaptive strategies, optimized resilient determinant, and moving forward. Trust and support from family are the key factor of resilient process and also be a resilient foundation for each respondent.Keywords: Resilient formation, resilient determinant, thalassemia